OC-029 Radiofrequency Ablation (Rfa) Confers Sustained Benefit for Squamous High Grade Dysplasia (Hgd) and Early Squamous Cell Carcinoma (Scc) in Patients who do not Progress following First Treatment. (4th June 2013) - Haidry, R J; Banks, M; Butt, M; Gupta, A; Louis-Auguste, J; Dunn, J; Smart, H L; Bhandari, P; Smith, L-A; Willert, R; Fullarton, G; Pietro, M di; et al.
Abstract : Introduction: Oesphageal SCC carries a poor prognosis. Squamous HGD is the precursor lesion to SCC. Risk of progression to SCC with HGD can be 65% at 5 years. RFA is a minimally invasive technique with proven efficacy for early neoplasia arising in Barrett's oesophagus. We present prospective data from 10 centres in the United Kingdom (UK) HALO registry. Methods: Superficial lesions were removed by endoscopic mucosal resection (EMR) before RFA. Treatment consisted of a single ablation at 12J/cm2. Patients were followed up 3 months after treatment with biopsies. Those with residual dysplasia underwent further RFA until 12 months when they were assessed for treatment success or failure. Recurrent dysplasia was retreated with EMR/RFA. Primary outcomes were reversal of dysplasia (CR-D) at 12 months. Results: 26 patients had RFA. Mean length mucosa ablated was 5.3 cm (1–14). 7/26 (27%) had EMR before RFA. Prior EMR did not confer benefit to outcome, nor did baseline disease length. Following first RFA, 6/26 patients (23%) progressed to invasive disease. Only one more patient progressed later in treatment course. CR-D was achieved in 50% at protocol end, mean 1.7 RFA treatments (1–4). 10/13 (77%) with successful RFA at 12 months remain disease free at most recent follow up (median 21 months). Kaplan Meier statistics show 2 years post treatment 68% patients are likely to remain in remission from dysplasia for those with successful outcome at 12 months. 5 patients (19%) required dilatations for oesophageal stricturing. Conclusion: Squamous HGD & CIS are aggressive pathologies as evidenced by the fact that 23% patients in our cohort progressed to invasive disease despite RFA. However the majority who do not progress early (13/19 patients) achieve benefit & are more likely to have a successful & durable outcome. There is limited experience in the UK with RFA in these patients. Pre RFA EMR for visible lesions is limited in our series. As a result some patients may be under staged prior to RFA which may account for the high rate of progression after first treatment. Disclosure of Interest: None Declared